Comparison of Copra Drying Performance Using a Modified Hybrid Solar Collector Dryer versus Conventional Drying - Sasmita Jamalu (PROGRAM STUDI MESIN DAN PERALATAN PERTANIAN, 2025)
Drying is an important postharvest process for reducing the moisture content of copra and maintaining its quality during storage. Conventional drying methods that rely on ambient conditions are strongly influenced by weather and temperature fluctuations, resulting in relatively slow and less controlled drying. This study evaluated the performance of a modified hybrid greenhouse dryer for copra drying by comparing its drying conditions with drying under ambient conditions. The experiment was conducted for five hours by monitoring drying temperature, initial and final moisture content, and moisture reduction rate. The results showed that the maximum temperature in the hybrid greenhouse dryer reached 45 °C, while the ambient drying condition reached 40 °C. The moisture content of copra dried using the hybrid system decreased from 65.91% to 11.61%, whereas the ambient-dried sample decreased from 52.51% to 16.88%. The corresponding moisture reduction rates were 10.86 %/h for the hybrid system and 7.13 %/h for ambient drying, indicating a 52.40% higher reduction rate in the hybrid system during the test period. The improved drying performance was associated with the utilization of solar energy through the collector, air circulation using a blower, and the thermal contribution of stone material within the drying system. Although the initial moisture contents differed between the two samples, the results indicate that the hybrid greenhouse dryer provided a more favorable drying condition and greater moisture reduction over the same drying period. Further studies should use uniform initial moisture content, sufficient experimental replications, and additional thermal-efficiency measurements to provide a stronger evaluation of system performance.